The Clinical Usefulness of IgE Antibodies Against Egg White and Its Components in Korean Children - Min, Taek Ki (The Korean Academy of Asthma, Allergy and Clinical Immunology; The Korean Academy of Pediatric Allergy and Respiratory Disease, 2013)
PURPOSE: Egg (egg white) allergies are among the most common food allergies in infants and young children. Serum egg white-specific IgE (sIgE) levels have been shown to be correlated with clinical symptoms, and the predictive decision point of sIgE levels has been proposed and used widely in the clinical setting. However, some patients whose sIgE levels to egg white are higher than the predictive decision point value show no clinical symptoms, and vice versa. This study was conducted to evaluate the clinical usefulness of sIgE antibodies to egg white and its components in the diagnosis of egg allergies. METHODS: Forty-one patients younger than 2 years of age with no experience of egg intake due to concerns regarding allergies or a non-specific clinical response to eggs were enrolled. Total IgE levels and the levels of IgE antibodies specific for egg white and its components (ovomucoid, ovalbumin, and conalbumin) were measured by ImmunoCAP testing. The clinical response of the subjects was confirmed by an open oral food challenge (OFC). RESULTS: Fifteen (71.4%) out of 21 patients in the egg white-sIgE ≥2 kU/L group showed a positive response, while 10 (50.0%) out of 20 patients in the egg white-sIgE <2 kU/L group showed a negative response to the OFC. There were no statistically significant differences in the levels of sIgE antibodies against egg white and its components between the positive and negative open OFC groups. In addition, there were no statistically significant differences in the levels of sIgE antibodies against egg white and its components based on an intra-group analysis. CONCLUSIONS: Our results show that the sensitivity and specificity of the predictive decision point values for egg white-sIgE antibodies by ImmunoCAP were relatively low in Korean children. In addition, no egg white component predicted the clinical reactivity of the subjects. We suggest that the predictive decision point value for a positive egg oral challenge test by ImmunoCAP should be re-evaluated. Moreover, we suggest that careful personal history recording and challenge tests are necessary for the correct diagnosis of an egg allergy.